Introducing University First Year Students to Academic Writing: Salient Issues - Muringani, Bertha; Kolobe, Maboleba (Journal La Edusci, 2024)
The present study investigated problems faced by first year students at the National University of Lesotho (NUL) as they try to adjust their writing into academic style. The research subjects were from the faculties of Humanities and Science and Technology. Data were collected from the students’ Communication and Study Skills (CSS) past examination papers (2018/2019). The study employed a descriptive design. A suitable analytical framework was crafted drawing from Appraisal and Metadiscourse theories. Also, some portions of the essays were analysed qualitatively to get a better understanding of the practices and also to identify common problems among students. The problems identified included citation incompetence, a limited repertoire of reporting verbs, poor academic writing style and some influence of creative writing. The study concluded that NUL first year students need more assistance to improve their academic writing skills and therefore recommended a number of solutions with more direct tutor intervention.